Diálogos (im)possíveis entre a terceirização da mão de obra feminina e o Direito Humano ao trabalho decente no Brasil - Portela, Anna Caroline Morlin (Universidade do Vale do Rio dos Sinos, 2022)
The present dissertation examines the outsourcing of female labour based on the human right to decent work, in order to examine whether or not the two concepts are in harmony, considering the brazilian context. The dissertation in question intends to investigate to what extent the outsourcing of female labour and the human right to decent work can dialogue. To assess whether or not the outsourcing of female labour is in line with the human right to decent work, this study is divided into two chapters, with a research method based on dialectical materialism. First, it is necessary to understand the meaning of work for contemporary capitalist society. From this conception, we seek to understand how gender and work are articulated to form the concept of sexual division of labour. After assessing the consequences of the link between gender and work, the notion of working class is defined for the present day, prioritizing the conceptualization of class from a gender perspective. Afterwards, the notion of outsourcing and its impacts on the world of work are examined, mainly from outsourced workers. Afterwards, the concept of decent work is analyzed, based on the understanding of the International Labor Organization (ILO) on the subject. At the end of this dissertation, it is observed how the outsourced work relationship, especially with regard to Brazilian workers, is not in accordance with the human right to decent work, approaching to the concept of social precariousness of labour, which presents itself as an antagonistic conception of decent work.
Keywords: Trabalho; Gênero; Divisão sexual do trabalho; Terceirização; Trabalho decente; Labour; Gender; Sexual division of labour; Outsourcing; Decent work; ACCNPQ::Ciências Sociais Aplicadas::Direito